Overeducation and local labour markets in Spain - Raul Ramos; Esteban Sanromá (Institute for the Study of Labor (IZA), 2011)
The objective of this paper is to analyze the influence of individual variables and some characteristics related to spatial mobility in regional labour markets on overeducation in Spain. With this aim, we use microdata from the Spanish Budget Family Survey to estimate a logit model for overeducation probability taking into account the problem of selection bias and the presence of data of different levels (individuals and territory). The obtained results permit us to conclude that the size of local labour markets and the possibility of extending the job search to other labour markets through commuting are relevant factors to explain overeducation in the Spanish labour market. In spite of the differences in terms of labour market institutions, our results are very similar to the ones obtained for other countries.
urn:nbn:de:101:1-201110263714
Keywords: J61; J24; J31; 330; educational mismatch; Spain; multilevel; commuting; job mismatch; differential overeducation; Unterbeschäftigung; Regionale Arbeitsmobilität; Regionaler Arbeitsmarkt; Spanien